2005
DOI: 10.1097/00042192-200512020-00008
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation, cognitive performance, and hormone therapy in postmenopausal women

Abstract: In postmenopausal women, sleep deprivation impaired visual functions and attention. However, this effect was not prolonged because after one rebound night the performance was improved, compared with baseline. Hormone therapy did not modify the cognitive performance during sleep deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 24 publications
5
133
0
5
Order By: Relevance
“…Despite this shared neural basis of memory, attention and alertness in some target brain areas for estrogen, the possible modulating effects of estrogen on reaction times and vigilance during sleep deprivation have so far not been considered. In a recent study, no modulating effect of estrogen on visual memory and shared attention during sleep deprivation was found (Alhola et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Despite this shared neural basis of memory, attention and alertness in some target brain areas for estrogen, the possible modulating effects of estrogen on reaction times and vigilance during sleep deprivation have so far not been considered. In a recent study, no modulating effect of estrogen on visual memory and shared attention during sleep deprivation was found (Alhola et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Given that the angular gyrus has been shown to be involved in multiple functions (Seghier, 2013) including memory retrieval and attention, the SD-induced alteration appears to be related to the decline in cognitive performance caused by sleep loss (Alhola and Polo-Kantola, 2007). Essentially, these results suggest the potential application of the new approach to studies of individual differences.…”
Section: Resultsmentioning
confidence: 94%
“…For example, sleep loss has been shown to reduce performance on a broad range of tasks (Alhola and Polo-Kantola, 2007). A recent study has showed that long-term SD significantly reduces the thalamic gray matter volume .…”
Section: Discussionmentioning
confidence: 99%
“…It is also noticeable that changes in cognitive performance and sleep pattern and quality are often associated with sex hormones (23,24). These findings highlight the importance of sex hormones in sleep regulation in the menopause period in females who indicate low levels of circulating estrogen (25) and are more sensitive to deleterious effects of sleep deficit on cognitive function (26).…”
Section: Introduction and Statement Of The Problemmentioning
confidence: 86%